EVALUATING THE LANDSCAPE DESIGN OF 3RD GENERATION SPACES THROUGH A STUDIO STUDY - AYAN ÇEVEN, Elif (Prizren Social Science Journal, 2022)
The transformation of the concept-form relationship into a concrete expression in the design experience, which is considered a challenging process, is one of the essential parts of this process. In this process, in which various methods are evaluated, the form seen as a communication tool occurs through distinct connotations. Within the scope of this study, students' search for form in a landscape design project problem, their connotations in the education process, and thus their solutions to the design problem were evaluated. In the study, the studies of the students made during a semester were criticized in the presence of the coordinator. The concept of coffee and its associations in the landscape design of the 3rd Generation coffee sales unit in a campus venue, the sources they inspired and their final projects constitute the material of this study. The concept-form relationships of the projects were examined and, as a result, it was determined that it was easier for students to transfer certain formal objects to the projects in the search for form.
Keywords: Social sciences (General); H1-99; Landscape Design, Concept, Form, 3rd Generation Cafe Landscape.; 4. Education